Nadzir's Responsibility for the Crime of Embezzlement of Waqf Assets by Other Parties Based on Indonesian Written Law - Faisal Faisal (International Journal Reglement & Society (IJRS), 2020)
Law Number 41 of 2004 Article 11, states that: